2015
DOI: 10.4172/2161-1009.1000172
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Potential of Phycobiliproteins: Role in Anti-Aging Research

Abstract: Aging research has made significant progress over recent years, particularly after the formulation of 'Oxidative stress theory of aging'. According to this theory, aging and its associated abnormalities may be prevented, at least to some extent, by application of certain antioxidants. Cyanobacterial phycobiliproteins (PBPs), the major light harvesting pigment proteins are widely characterized for their in vivo and in vitro antioxidant activity. Since, reactive oxygen species (ROS) are considered as important f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 52 publications
0
29
0
1
Order By: Relevance
“…This compound, is used as a food coloring and has a great antioxidant (Patel et al, 2006;Sonani et al, 2015), anti-inflammatory, immunomodulatory and anti-cancer properties (Hirata et al, 2000;Romay et al, 2003;Patel et al, 2004;Eriksen, 2008). Sarada et al (1999) studied the stability of phycocyanin, and observed stability for 4 weeks in a pH range of 5-7.5 at 25°C and 9°C.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This compound, is used as a food coloring and has a great antioxidant (Patel et al, 2006;Sonani et al, 2015), anti-inflammatory, immunomodulatory and anti-cancer properties (Hirata et al, 2000;Romay et al, 2003;Patel et al, 2004;Eriksen, 2008). Sarada et al (1999) studied the stability of phycocyanin, and observed stability for 4 weeks in a pH range of 5-7.5 at 25°C and 9°C.…”
Section: Discussionmentioning
confidence: 99%
“…The AP of the Spirulina powder samples was evaluated in a lipid system consisting of soybean oil, according to the methodology proposed by Souza et al (2006). In 1000 mL beakers, 250 mL of soybean oil and 1 g of Spirulina platensis powder were added.…”
Section: Antioxidant Potential (Ap) Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in this Section the toxicology and potential health/medicinal effects and applications of phycobilins and phycobiliproteins are discussed. For further details about the roles of dietary phycocyanin [60,99] and phycobiliproteins [120] in animals and humans the readers are directed to the above-mentioned reviews [60,99,120].…”
Section: Health Promoting and Medicinal Effectsmentioning
confidence: 99%
“…A new medicinal aspect of phycobiliproteins and their antioxidant properties is their potential use in anti-aging research (reviewed in [120]). For instance, phycoerythrin purified from Lyngbia and applied as dietary supplement improved the mean life span, moderated the decline in agingassociated physiological functions, enhanced stress tolerance, and also showed positive effects on an Alzheimer's disease model in a transgenic Caenorhabditis elegans CL4176 model [137,138].…”
Section: Antioxidant Effectmentioning
confidence: 99%